The directorial analysis of the text of culture (graphical, historical, dramatic, etc.) in exercises of a mental experiment (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2019)
The article actualizes the problem of mastering the Method of Event-ActionAnalysis by the students of theatrical schools. The author of the article proposes thepropaedeutical practical stage of the Method application. The stage makes abstract and specific structures meet in the creative analyses of very different texts of culture like paintings, landscapes, historical events and even the laws of nature.The article offers the examples of creative works of the students of Novosibirsk drama school in application the Method of Event-Action Analysis to cultural texts.